2014
DOI: 10.1074/jbc.m114.598763
|View full text |Cite
|
Sign up to set email alerts
|

IκB Kinase β (IKBKB) Mutations in Lymphomas That Constitutively Activate Canonical Nuclear Factor κB (NFκB) Signaling

Abstract: Background: How IB kinase␤ K171E and K171T mutations mediate lymphomagenesis is not known. Results: We performed biochemical, molecular modeling and TALEN-based knockin studies on wild-type and mutant IKK␤. Conclusion: Mutant IKK␤ molecules are constitutively active in an activation-loop phosphorylation-independent manner. Significance: These results have broad implications for the function of positively charged residues in all activation loop-dependent kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…We see mutations in oncogenes and tumor-suppressor genes in HepG2, such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016), as well as in the Wnt-pathway gene CTNNB1 due to the presence of either HepG2-specific protein-altering changes or small-scale structural changes (Table S5, Table S6, Dataset 1, Dataset 4, Supplemental Data). Moreover, we also identified mutations in genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). These mutations also implicate the dis-regulation of their associated molecular pathways in HepG2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We see mutations in oncogenes and tumor-suppressor genes in HepG2, such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016), as well as in the Wnt-pathway gene CTNNB1 due to the presence of either HepG2-specific protein-altering changes or small-scale structural changes (Table S5, Table S6, Dataset 1, Dataset 4, Supplemental Data). Moreover, we also identified mutations in genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). These mutations also implicate the dis-regulation of their associated molecular pathways in HepG2.…”
Section: Discussionmentioning
confidence: 99%
“…The gene overlap between HepG2 PPA and the Sanger Cancer Gene Census is 19 (Table S6). HepG2 PPA variants include oncogenes and tumor suppressors such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016) as well as other genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). RP1L1, which was recently found to be significantly mutated in hepatocellular carcinoma (Cancer Genome Atlas Research Network 2017) is also present among the PPA variants.…”
Section: Snvs and Indelsmentioning
confidence: 99%
“…The NFκB pathway is required for normal marginal zone B cell development (Cariappa et al, 2000;Xie et al, 2007). In the study by Kai et al, the introduction of heterozygous and homozygous IKKβ K171E mutations into the human Burkitt's lymphoma BJAB cells by TALEN mutagenesis resulted in constitutive activation of the NFκB pathway (Kai et al, 2014). Moreover, K171E IKBKB knock-in BJAB cells were more resistant to apoptosis, as demonstrated by a significant increase in BCL2 expression (Kai et al, 2014).…”
Section: Lymphoid Disordersmentioning
confidence: 96%
“…Given that ZFN-, TALEN-and CRISPR-based mutagenesis offers the possibility of generating heterozygous and homozygous knock-ins, genome editing technology is a valuable tool for deciphering the impact of a gene mutation. Kai et al have used TALEN-based mutagenesis to study the K171E and K171T mutations in the IκB kinaseβ (IKKβ) protein that are found in splenic marginal zone lymphomas and multiple myeloma (Kai et al, 2014). IKKβ, encoded by the IKBKB gene, is the critical activating kinase in the canonical nuclear factor κB (NFκB) pathway (Rossi et al, 2011;Rossi et al, 2012;Ukaji and Umezawa, 2014).…”
Section: Lymphoid Disordersmentioning
confidence: 99%
“…Aberrant NF-kB signaling has been described in various cancers and immune diseases. Gene variants of IKKb have been associated with colorectal cancer (12), lymphomas, multiple myeloma (13), and combined immunodeficiency (14). Previous work has also identified variants of MYD88 and TNFRSF11A that promote constitutive activation of NF-kB (15,16).…”
mentioning
confidence: 99%